Burno leto Prekmurca Jožefa (Bonaventure) Godine od decembra 1918 do septembra 1919 - Hozjan, Andrej (Prispevki za novejšo zgodovino, 2020)
The article at hand represents a detailed analysis of a single year in the life and work of Jožef Godina (1898-1986), a survivor of World War I, patriot, Maister's fighter, national activist, monk, priest, editor, and publicist. The two short introductory chapters present Godina's family tree, focusing on his parents as well as his life between his birth and the day before Christmas of 1918. This section is followed by an extensive description of Godina's days between 24 December 1918 and his escape from captivity at the beginning of February 1919 as well as the period between March and September 1919. Godina certainly belongs among the most laudable inhabitants of the Prekmurje region: he strived tirelessly on all fronts and even risked his life to ensure the annexation of this region to the Kingdom of SHS.
Keywords: annexation of Prekmurje; Godina, Jožef; Maister's fighters; Maistrovi borci; Prekmurje; priključitev Prekmurja; SHS; Slovene history; slovenska zgodovina